2010
DOI: 10.1002/ieam.104
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐based analysis of polychlorinated biphenyl toxicity in harbor seals

Abstract: Persistent organic pollutants (POPs) have been associated with adverse health effects in marine mammals. However, the complex mixtures to which free-ranging populations are exposed constrain the elucidation of cause-and-effect relationships between specific POPs and the observed health risks. In this study, we 1) assembled data from studies showing polychlorinated biphenyl (PCB)-associated effects on the health of free-ranging harbor seals in the northeastern Pacific Ocean, 2) carried out additional POP analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 39 publications
(70 reference statements)
3
56
2
Order By: Relevance
“…Predicting PBDE Concentrations and Assessing Health Risk Related to PCB-SQC Under the hypothetical scenario where resident killer whales are confined to spending 100 % of their time in the Arch Environ Contam Toxicol Strait of Georgia, observed concentrations of P PBDE in SRKW exceeded both the PBDEs' upper limit threshold level for endocrine disruption (1.5 mg/kg lipid) established in grey seals (Hall et al 2003) and the recent harbor seal PCB-TEC threshold (1.3 mg/kg lipid; Mos et al 2010), as illustrated in Fig. 1.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Predicting PBDE Concentrations and Assessing Health Risk Related to PCB-SQC Under the hypothetical scenario where resident killer whales are confined to spending 100 % of their time in the Arch Environ Contam Toxicol Strait of Georgia, observed concentrations of P PBDE in SRKW exceeded both the PBDEs' upper limit threshold level for endocrine disruption (1.5 mg/kg lipid) established in grey seals (Hall et al 2003) and the recent harbor seal PCB-TEC threshold (1.3 mg/kg lipid; Mos et al 2010), as illustrated in Fig. 1.…”
Section: Resultsmentioning
confidence: 98%
“…Data for PCB-TECs included the revised harbor seal PCB toxicity threshold (1.3 mg/kg lipid) developed by Mos et al (2010); the bottlenose dolphin PCB toxicity threshold (10 mg/kg lipid) reported by Hall et al (2006); and, a previous harbor seal PCB toxicity threshold (17 mg/kg lipid) published formerly by Ross et al (1996) (Table S9 in supporting information). Interestingly, the PBDE-TEC adopted here falls within the range of these PBC-TEC values reported for marine mammals.…”
Section: Pbde Health Risk Assessmentmentioning
confidence: 99%
“…Likewise, concentrations of DDT in human breast milk from Japan have not decreased since 1998 (Kunisue et al 2006). DDT concentrations in Galapagos sea lion pups are lower than those detected in pinnipeds from the Northern Hemisphere (Kajiwara et al 2001;Kannan et al 2004;Debier et al 2005;Del Toro et al 2006;Blasius and Goodmanlowe 2008;Mos et al 2010), but greater than those detected recently in adult subdominant males, adult females, juveniles and pups of southern elephant seals (Mirounga leonina) from Elephant Island, Antarctica (Miranda-Filho et al 2007). Interestingly, Galapagos sea lion pups exhibited DDT concentrations similar to those detected in juveniles of Hawaiian monk seals (Monachus schauinslandi) from several subpopulations in the Northwestern Hawaiian Islands (Ylitalo et al 2008).…”
Section: The Ddt Legacy Continuesmentioning
confidence: 84%
“…DDT concentrations in Galapagos sea lion pups are near levels expected to be associated with impacts on the immune systems, and in minor degree on the endocrine systems in males. Adult male Galapagos sea lions can be expected to exhibit DDT concentrations that are higher than those in pups as DDTs accumulate throughout the animal's life because they are unable to offload contaminants during reproduction [35].While concentrations of DDTs pose protracted health risk because of lifetime exposure, the ∑PCB concentrations in Galapagos sea lion pups were lower than the new toxicity reference value of1,300 μg/kg lipid for risk of immunotoxicity and endocrine disruption in harbor seals [67]. Other POPs with a similar mode of toxicity such as polybrominated diphenyl ether (PBDEs) flame retardants, which were also detected recently in these animals [34], can further exacerbate the immune and endocrine response.…”
Section: Health Risk Assessmentmentioning
confidence: 92%